New directors in Bulgarian short film of the last decade - Alexandrova, Petia (Young Scientific Music and Dance Forum : Conference with international participation, 2021)
Today, a film director rarely makes a debut straight into the big-screen cinema. Typically, it begins either in television or in short cinema, and sometimes together. The text considers two options: 1 The short films of the already established directors Nadezhda Kosseva, Svetla Tsotsorkova, Dragomir Sholev, Kristina Grozeva and Petar Valchanov 2. The short films of directors who are yet to have their debuts on the screens: Toma Vasharov, Nikolay Todorov, Pavel Vesnakov. The thesis is that they state their specific visual style in the short films, their choice of actors and dramaturgy – choices that will follow in feature films. However, they don‘t engage in the thought of viewership success, which makes them freer in self-expression.